Investigation of energy generation potential ofreverse electrodialysis fed with synthetic and real solutions - Zoungrana, Ali (My University, 2020)
In addition to being quantitatively limited, fossil fuel is negative to the earth by inducing climate change. The energy transition is inevitable, and many alternatives and renewable energy sources are being considered to replace fossil fuels. Hydropower, wind and solar energy are leaders in the renewable energy world, but huge and accessible other energy sources such as salinity gradient power (SGP) exist and need to be collected to contribute to the energy demand. SGP is mainly extracted with reverse electrodialysis (RED) and pressure retarded osmosis (PRO) systems. A lab-scale RED module was constructed and used to monitor the energy generation potential of different water bodies and the parameters associated with the performance of the process. The optimal feed solutions concentration, flow rate and their importance in improving the power density in RED were investigated and the experimental results showed that increasing the flow rate is beneficial by augmenting the power output of RED, but too high, it harms the process performance. The results demonstrated that the voltage and the stack resistance increased with increasing number of cell-pairs but the increasing trend of the voltage decreased from the linear trend due to the stack resistance. Lastly, the RED power output performance with treated different municipal wastewaters was investigated together with natural seawater and synthetic solutions. The synthetic solutions resulted in the highest power density. Among the wastewaters, ultrafiltration (UF) effluent was more attractive for RED compared to membrane bioreactor (MBR) and advanced biological treatment (ABT) effluents. The SEM-EDX analysis showed that Mg2+ and Ca2+ were present in natural solutions and may have contributed to reducing the power output. Although treated municipal wastewaters discharged into seawater are important sources of RED-SGP, feed solutions quality together with improved, highly selective and cost-effective ion exchange membranes (IEMs) are necessary to optimize the power output.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: Ion exchange membrane; Municipal wastewater; Renewable energy; Reverse electrodialysis; Salinity gradient power